Method and language - Grünfeld, Joseph (Amsterdam B.R. Grüner Publishing, 1982)
This monograph explores the relationship between method and language. The notion of method is inherent in everything we can claim to understand. The language conventions which make a question meaningful cannot be challenged at the same time the problem is posed. Problems exist only relatively to accepted ways of thinking and doing; verification or falsification can take place only when we agree what hypotheses are in question. Our ability to be rational and critical that is, to apply logic to our beliefs depends on the kinds of distinctions we are able to make in our language.